VAZIYATLARNI IMITATSIYALASH ASOSIDA OʻQUVCHILARDA TARIXIY TAFAKKURNI RIVOJLANTIRISHGA YOʻNALTIRILGAN PEDAGOGIK JARAYON MODELI - Seyfullaev, A.S. (SCIENCE and SOCIETY, 2024)
The article develops and examines the forms, methods, techniques of forming historical thinking and a model of the pedagogical process aimed at achieving this goal.
Keywords: historical reality; historical thinking; forms; methods; techniques for the formation of historical thinking; a model of a purposeful pedagogical process